Total quality management and performance of International Non-Governmental Organizations in Dar es Salaam, Tanzania. - Bavon, Christopher (Mzumbe University, 2026)
A dissertation submitted in partial fulfilment of the requirement for the award of the degree of Master of Business Administration in Corporate Management (MBA-CM) of Mzumbe University.